Prevention is the best way to health - Cates, Michael B. (My University, 2009)
Health is an essential element of military readiness, and prevention is and always will be the best way to health. Preventing diseases and conditions that threaten the health of the warfighter is more operationally sound since it maximizes available manpower. It is more beneficial to the Soldier, from a well-being perspective, to stay healthy and avoid all that the hospital has to offer, such as long waiting room times, diagnostics, and treatment. When considering healthcare costs, both short-term and long-term, prevention again wins out. In an ideal world, the military would be able to minimize disease and nonbattle injuries (DNBI), through prevention and health promotion, while optimizing the restorative medicine resources and applying them toward those diseases and conditions that are not readily preventable, especially combat injuries. This article takes a brief look at military preventive medicine, its background, its current status, and some future considerations for its use in improving the health of our warfighters.
Keywords: Military readiness; Preventive medicine; Health; Proactive approaches; Soldier well-being